Complexities of organisational change: the case of the Eastern Cape Department of Education (ECDE) - Ngoma, Wendy Yolisa (My University, 2009)
For rational theories of organisational change, organisational dysfunctionalities are nothing more than the inadequacy of organisations to maximise on their goals or lack of co-ordination of different types of inputs and processes. Usually, such observations are made in exclusion of the analysis of organisational realities and the experiences that are part of their daily realities. This thesis explores the experiences of organisational change in a single case of the provincial department of education, namely the Eastern Cape Department of Education (ECDE). Using the qualitative and exploratory methods of interviews and document analysis, it asks how and why the department was perceived to be in a state of crisis in terms of service delivery, eight years after its initial transformation. To explore these questions, the thesis looked at the interplay between context, organisational design and internal skills and capacities, as the triad of processes that influenced the patterns for organisational change in this context. Broadly, the findings revealed that issues of organisational efficiency and service delivery cannot be debated and analysed outside of the political processes that influence them. The ECDE revealed that it was caught in endless politics of networks of coalition which influenced the pattern of service delivery. As a result this thesis concluded that organisational change and service delivery debates have to extend beyond the rational inputs and outputs paradigms to look at the complexities of networks that were a coincidence of transitional politics. It therefore proposes a focus on relational and network analysis of organisations to unravel their politics and pattern of influence on service delivery.
Keywords: organisational change; organisational design; service delivery; social antagonism; power; politics; skills and capacity; service delivery; inefficiency